Strategi Perencanaan Destinasi Tukad Bindu sebagai Daya Tarik Wisata di Kota Denpasar - I Made Darsana; Francisca Titing Koerniawaty (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Tukad Bindu, a river tourism site in Denpasar, Bali, attracts a significant number of domestic tourists. However, it currently lacks a well-defined strategic plan for sustainable development, which is crucial for establishing it as a competitive tourist destination in Denpasar City. This study aims to identify the development potential along Tukad Bindu, Denpasar, Bali, using qualitative methods and SWOT analysis. The research primarily focuses on river revitalization as a catalyst for tourism, enhancing agricultural productivity, tourist attractions, and fostering active community involvement. The findings suggest that the SO (Strengths-Opportunities) strategy can be employed by maintaining river revitalization as a key driver for tourism while also boosting agricultural productivity and tourist attractions. The ST (Strengths-Threats) strategy involves empowering the community through active participation to mitigate potential threats. The WO (Weaknesses-Opportunities) strategy is facilitated by providing educational programs through the Denpasar City Environmental Service to the surrounding community. Meanwhile, the WT (Weaknesses-Threats) strategy underscores the importance of collaboration with the government and private sector to improve tourism promotion, develop cultural and agricultural tourism attractions, and ensure the sustainability of future programs. This study recommends the adoption of these strategies as concrete steps to fully leverage the development potential around Tukad Bindu, Denpasar, Bali. The successful implementation of these strategies is anticipated to positively impact tourism, agriculture, and the welfare of the local community.